(untitled) (Journal of Forensic Medicine & Toxicology, 2025)
ICD – 10, also known as the International Statistical Classification of Diseases, is the international standard for defining and reporting diseases, conditions and external causes that lead to the mortality or morbidity, thus aiding in comparison and sharing of health information using a standardized, common language. ICD is used by physicians, nurses, research ers, health information managers and coders, health information technology workers, policy makers, insures and patient organizations. Most countries use this system to report mortality data, which is a key indicator of health status. The pres ent study has been conducted as a one-year retrospective study and one year prospective study, giving emphasis on the history taking part of medicolegal postmortem examinations conducted in GMCH, Chandigarh. The aim of the study was to identify the defects in history taking by the use of Chapter XX of ICD-10, which focuses on the external causes of mortality.